Teacher as a peace leader: A new peace linguistic approach to “Freedom Writers” - Chandra, Yuliyanto (Englisia Journal, 2023)
The role of a language teacher as a character educator and peace-builder is sometimes undermined by the pervasive thinking that language teaching solely entails transference of knowledge about language. However, it is a fallacy that language teaching is not facilitative of character development. Since language has the power of creating peace and even war, this study seeks to interrogate how a language teacher as a leader in a classroom can be a model of peacebuilding through language use. Using New Peace Linguistics (henceforth NPL)—a newly emerging framework in linguistics and peace studies—this study analyzed the pragmatics, specifically the speech acts, as found in Erin Gruwell’s utterances in “Freedom Writers”, a movie about teacher who has to deal with a group of rebellious students. The study found that Erin Gruwell mostly used mediating, expressing empathic concern, complimenting, disciplining, apologizing, giving instruction, and encouraging for creating peace, healing traumatic experiences, and changing the students’ behavior.